Preparation and application of multi-doped and coated composite layered positive electrode material
Through the multi-doped and coated composite layered positive electrode material preparation method, the problem of unstable structure of the lithium-ion battery positive electrode material under high voltage is solved, and the high specific capacity and cycle stability are improved, and the cost is low and suitable. Mass production.
Patent Information
- Application Number
- CN202411445936.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
AI Technical Summary
The existing irreversible oxidation reaction of the positive electrode materials of existing lithium-ion batteries at high voltages leads to structural instability, resulting in rapid capacity loss and voltage attenuation. The existing modification methods are costly and difficult to commercialize, and the material morphology is poor.
Using a multi-doped and coated composite layered positive electrode material preparation method, doped and sulfate is obtained by grinding the layered positive electrode material precursor, lithium source, aluminum source, titanium source and sulfate in anhydrous ethanol, and calcining is carried out in one-step to obtain doped and The coated composite material uses the synergistic effect of Ti doping and sulfate to improve the structural stability of the material and the lithium ion transport efficiency.
It significantly improves the specific capacity and cyclic stability of the positive electrode material at high voltage, reduces side reactions, and improves the lithium ion transmission rate. The material is cheap and has good morphological uniformity, which is suitable for large-scale production.
Smart Images

Figure CN119208574A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of a multi-doped and coated composite layered positive electrode material, belonging to the lithium ion battery technology part in the electrochemical field. Background Art
[0002] Lithium-ion batteries have been widely used in consumer electronics, but they still cannot meet people's needs for grid energy storage and electric vehicle daily performance. At present, most commercial lithium-ion batteries still use lithium iron phosphate as the positive electrode, which has a relatively low energy density. Therefore, the development of high-energy-density lithium-ion batteries is urgently needed, and finding high-capacity positive electrode materials is the key to achieving high-energy-density lithium-ion batteries. High-nickel layered oxides, which can show more specific capacity at higher cut-off voltages and have low cost, are considered to be a very promising positive electrode material that meets the requirements of high-energy-density lithium batteries.
[0003] However, due to the overlap of electron orbitals, the release of lithium ions from high-nickel layered oxides at high cut-off voltages is often accompanied by the redox of oxygen anions. Irreversible oxygen evolution accelerates the decomposition of the electrolyte and the structural phase change of the positive electrode material, which inevitably triggers the adverse migration and structural distortion of the transition metal during the cycle, causing the positive electrode material to exhibit rapid capacity loss and voltage decay. Therefore, improving the high-voltage structural stability of the positive electrode material and inhibiting irreversible oxygen-related reactions are the key to achieving high-voltage and long-cycle stability of high-nickel materials.
[0004] Doping and coating are common modification methods for layered oxide cathode materials. It has been found that doping and surface coating can improve the performance of layered cathode materials under high pressure conditions in different aspects. Among them, Al doping can effectively inhibit cation mixing and prevent structural phase change caused by excessive lithium removal. Ti doping can change the internal defects of the material and increase the structural stability of the material. S negative ion doping can stabilize the oxygen layer and reduce O 2- Participate in the reaction. Lithium sulfate is coated on the surface of the layered material, which can not only isolate the electrode material and the electrolyte, reduce the side reactions, but also improve the lithium ion transmission efficiency. However, these single modifications can only play a certain role in one-sidedness for high-nickel positive electrode materials. The comprehensive improvement of high-voltage performance is insufficient and cannot meet people's pursuit of the performance of high-nickel positive electrode materials. The composite modification methods are mostly complex and costly, making it difficult to commercialize, and the prepared materials have poor morphology uniformity. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a preparation and application of a multi-doped and coated composite layered positive electrode material.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A multi-doped and coated composite layered positive electrode material, the material is prepared by the following method, the method steps are as follows:
[0008] (1) grinding and mixing layered cathode material precursor powder, lithium source, aluminum source, titanium source and sulfate in anhydrous ethanol to obtain a mixed powder;
[0009] (2) placing the mixed powder into a crucible, and then placing the crucible into a heating device, first heating it to 480° C. to 520° C. for pre-sintering for 4 h to 6 h, then heating it to 600° C. to 1000° C. for calcining for 8 h to 15 h, and cooling it down after the calcination to obtain a multi-doped and coated composite layered positive electrode material in the crucible;
[0010] Among them, the molar ratio of the layered positive electrode precursor sample material to the lithium source sample material is 1:1.05~1.2, the amount of the aluminum source is 0.2%~5% of the amount of the layered positive electrode material precursor powder, and more preferably 0.5%~1.5%; the amount of the titanium source is 0.2%~5% of the amount of the layered positive electrode material precursor powder, and more preferably 0.5%~2%; the amount of the sulfate ion is 0.7%~10% of the amount of the layered positive electrode material precursor powder, and more preferably 1%~3%.
[0011] The sulfate radical comes from lithium sulfate, aluminum sulfate and titanium sulfate.
[0012] Preferably, in step (1), the layered cathode material precursor powder is (Ni x A y M 1-x-y )(OH)2、(Ni x A y M 1-x-y )CO3 or (Ni x A y M 1-x-y )C2O4, wherein A is Co or Fe, M is Mn or W, 0 <x<1,0≤y<1,0≤1-x-y<1。
[0013] Preferably, in step (1), the lithium source sample may be lithium sulfate, lithium carbonate, lithium hydroxide or lithium oxalate.
[0014] Preferably, in step (1), the aluminum source sample may be aluminum sulfate, aluminum acetate, aluminum carbonate, or aluminum oxalate.
[0015] Preferably, in step (1), the titanium source sample may be titanium dioxide, tetrabutyl titanate or titanium sulfate.
[0016] Preferably, in step (1), during grinding, the relative humidity is 5% to 20%, the temperature is 30° C. to 60° C., and the grinding time is 0.5 h to 2 h. When the lithium source or titanium is a moisture-sensitive substance such as lithium hydroxide or tetrabutyl titanate, the material can be effectively prevented from absorbing water by controlling the grinding conditions.
[0017] Preferably, in step (2), during the heating process, the temperature increase rate is 2°C / min to 15°C / min, and during the cooling process, the temperature decrease rate is 1°C / min to 10°C / min.
[0018] Preferably, when the nickel content in the layered cathode material precursor powder is greater than 0.8 in step (1), the high temperature heating device in step (2) is a tube furnace, the atmosphere is oxygen, and the gas flow rate is 50 cfm to 300 cfm. Otherwise, a muffle furnace is used, and the atmosphere is air.
[0019] Preferably, the particle diameter of the multi-doped and coated composite layered positive electrode material is 1 μm to 15 μm, wherein the doping amount of Al element is 0.2% to 5% of the amount of substance of the layered positive electrode material, the doping amount of Ti element is 0.2% to 5% of the amount of substance of the layered positive electrode material, the doping amount of sulfur anions is 0.2% to 5% of the amount of substance of the layered positive electrode material, and the coating amount of Li2SO4 is 0.5% to 5% of the amount of substance of the layered positive electrode material.
[0020] A lithium ion battery, wherein the positive electrode material of the battery adopts the multi-doped and coated composite layered positive electrode material described in the present invention.
[0021] Beneficial Effects
[0022] The present invention provides a multi-doped and coated composite layered positive electrode material, which uses a precursor mixed lithium source, aluminum source, titanium source and sulfate in a one-step method to obtain a multi-composite positive electrode material doped with anions and cations and coated with a fast ion conductor. The three doped ions play different roles in the material structure, and play a synergistic role in improving the high voltage performance of high nickel materials. 4+ The doping of Ni 2+ / Ni 3+ The ratio increases, and part of the sulfate is reduced to obtain S2 2- , will make you 2+ / Ni 3+The ratio is reduced, and the two reach a balance. In addition, the Li2SO4 fast ion conductor coating on the surface of the sulfate decomposition and synthesis material also shows its rigid protection mechanism and fast ion diffusion performance. Finally, through the synergistic effect of multiple doping and coating, it can not only reduce side reactions such as oxygen production at high voltage positive electrode, but also increase the lithium ion transmission rate and stabilize the internal lattice structure of the positive electrode in the high lithium desorption state, thereby significantly improving the specific capacity and cycle stability of the layered positive electrode material at high charge cut-off voltage.
[0023] The present invention provides a multi-doped and coated composite layered positive electrode material, which achieves the effect of multiple anion and cation doping and coating in one step by adding a modifying substance during the lithium mixing process. The method is simple and effective, low-cost, and the prepared material has good morphology uniformity and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an energy spectrum (EDS) diagram of the cross section of the composite layered positive electrode material prepared in Example 1.
[0025] Figure 2 This is the XPS data of the composite layered positive electrode material prepared in Example 1.
[0026] Figure 3 The electrochemical cycle performance diagram of the battery assembled with the positive electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0027] The present invention will be further described in detail below in conjunction with specific embodiments.
[0028] In the following examples or comparative examples:
[0029] Assembly of button cells: At room temperature, a working electrode is first prepared by mixing the material prepared in the example or comparative example with a conductive agent and a binder in a ratio of 8:1:1 to form a uniform slurry; then, the obtained slurry is evenly applied to an aluminum foil with a scraper, and vacuum dried at 100°C for 12 hours to obtain a working electrode; finally, a punching machine is used to press the aluminum foil coated with the sample into small discs with a diameter of 1.1 cm as the positive electrode, a lithium sheet as the negative electrode material, and a 1.0M LiPF6 carbonate electrolyte to prepare a button cell.
[0030] The electrochemical performance test was completed under the detection of the blue electric system, with a test voltage range of 3.0-4.6V, a test temperature of 30°C, and a current density of 1C (1C=200mA / g).
[0031] Example 1
[0032] The precursor (Ni 0.9 Co 0.05 Mn0.05 )(OH)2, LiOH, (CH3COO)3Al, TiO2 and Li2SO4 were mixed in a molar ratio of 0.98:1.00:0.01:0.01:0.02, and ground for 0.5 h at a relative humidity of 10% and a temperature of 45°C to obtain a mixed powder, which was loosely spread in a crucible, and then the crucible was placed in a tubular furnace, heated to 500°C at a rate of 5°C / min, and then pre-sintered for 5 h, and then heated to 750°C and calcined for 10 h in an oxygen atmosphere with a gas flow rate of 200 cfm, and finally cooled at a rate of 2°C / min to obtain a multi-doped and coated composite layered positive electrode material, denoted as Al 0.01 Ti 0.01 S 0.01 -Li(Ni 0.9 Co 0.05 Mn 0.05 )O2@Li2SO4.
[0033] The cross-sectional EDS test results of the composite layered cathode material are as follows: Figure 1 As shown, the results indicate that Al, Ti and S elements are uniformly distributed inside the composite material.
[0034] The XPS test results of the composite layered cathode material are as follows Figure 2 As shown, the results show that the Al in the composite material exists in +3 valence, Ti exists in +4 valence, and S element exists in SO4 2- and S2 2- exists in the form of.
[0035] The electrochemical cycling results of the assembled battery are shown in Figure 3 As shown in the figure, it can be seen that after 300 cycles, Example 1 still has a specific capacity of 183.1 mAh / g, and the capacity retention rate is 91.0%.
[0036] Comparative Example 1
[0037] The precursor (Ni 0.9 Co 0.05 Mn 0.05 )(OH)2 and LiOH were mixed in a molar ratio of 1.00:1.07, and anhydrous ethanol was added and ground for 0.5 h under the conditions of relative humidity of 10% and temperature of 45°C to obtain a mixed powder, and the mixed powder was loosely spread in a crucible, and then the crucible was placed in a tubular furnace, and the temperature was increased to 500°C at a rate of 5°C / min, and then pre-sintered for 5 h, and then heated to 750°C and calcined for 10 h, in an oxygen atmosphere with a gas flow rate of 200 cfm, and finally cooled at a rate of 2°C / min to obtain a layered positive electrode material, denoted as Li(Ni 0.9 Co 0.05Mn 0.05 )O2.
[0038] The electrochemical cycling results of the assembled battery are shown in Figure 3 As shown in the figure, it can be seen that after 300 cycles, Comparative Example 1 has a specific capacity of only 106.8 mAh / g, and the capacity retention rate is 54.1%.
[0039] Comparative Example 2
[0040] The precursor (Ni 0.9 Co 0.05 Mn 0.05 )(OH)2, LiOH, (CH3COO)3Al and TiO2 were mixed in a molar ratio of 0.98:1.07:0.01:0.01%, and anhydrous ethanol was added and ground for 0.5h under the conditions of relative humidity of 10% and temperature of 45°C to obtain a mixed powder. The mixed powder was loosely spread in a crucible, and then the crucible was placed in a tubular furnace, and the temperature was increased to 500°C at a rate of 5°C / min, and then pre-sintered for 5h, and then heated to 750°C and calcined for 10h in an oxygen atmosphere with a gas flow rate of 200cfm. Finally, the temperature was cooled at a rate of 2°C / min to obtain an aluminum-titanium co-doped composite material, denoted as Al 0.01 Ti 0.01 -Li(Ni 0.9 Co 0.05 Mn 0.05 )O2.
[0041] The electrochemical cycling results of the assembled battery are shown in Figure 3 As shown in the figure, it can be seen that after 300 cycles, Comparative Example 2 has a specific capacity of 155.6 mAh / g and a capacity retention rate of 79.8%.
[0042] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A multi-doped and coated composite layered positive electrode material, characterized in that: The material is prepared by the following method, and the method steps are as follows: (1) grinding and mixing layered cathode material precursor powder, lithium source, aluminum source, titanium source and sulfate in anhydrous ethanol to obtain a mixed powder; (2) placing the mixed powder into a crucible, and then placing the crucible into a heating device, first heating it to 480° C. to 520° C. for pre-sintering for 4 h to 6 h, then heating it to 600° C. to 1000° C. for calcining for 8 h to 15 h, and cooling it down after the calcination to obtain a multi-doped and coated composite layered positive electrode material in the crucible; Among them, the molar ratio of the layered positive electrode precursor sample material and the lithium source sample material is 1:1.05~1.2, the amount of the aluminum source is 0.2%~5% of the amount of the layered positive electrode material precursor powder, and more preferably 0.5%~1.5%; the amount of the titanium source is 0.2%~5% of the amount of the layered positive electrode material precursor powder, and more preferably 0.5%~2%; the amount of the sulfate ion is 0.7%~10% of the amount of the layered positive electrode material precursor powder, and more preferably 1%~3%. The sulfate radical comes from lithium sulfate, aluminum sulfate and titanium sulfate.
2. A multi-doped and coated composite layered positive electrode material as claimed in claim 1, characterized in that: In step (1), the layered cathode material precursor powder is (NixAyM1-xy)(OH)2, (NixAyM1-xy)CO3 or (NixAyM1-xy)C2O4, wherein A is Co or Fe, M is Mn or W, 0 <x<1,0≤y<1,0≤1-x-y<1。 3. A multi-doped and coated composite layered positive electrode material as claimed in claim 1, characterized in that: In step (1), the lithium source sample can be lithium sulfate, lithium oxalate, lithium carbonate, or lithium hydroxide; the aluminum source sample can be aluminum sulfate, aluminum carbonate, aluminum oxalate, or aluminum acetate; and the titanium source sample can be titanium dioxide, tetrabutyl titanate, or titanium sulfate.
4. A multi-doped and coated composite layered positive electrode material as claimed in claim 1, characterized in that: In step (1), during grinding, the relative humidity is 5% to 20%, the temperature is 30° C. to 60° C., and the grinding time is 0.5 h to 2 h. When the lithium source or titanium is a moisture-sensitive substance such as lithium hydroxide or tetrabutyl titanate, the material can be effectively prevented from absorbing water by controlling the grinding conditions.
5. A multi-doped and coated composite layered positive electrode material as claimed in claim 1, characterized in that: In step (2), during the heating process, the temperature increase rate is 2°C / min to 15°C / min, and during the cooling process, the temperature decrease rate is 1°C / min to 10°C / min.
6. A multi-doped and coated composite layered positive electrode material as claimed in claim 1, characterized in that: When the nickel content in the layered cathode material precursor powder is greater than 0.8 in step (1), the high temperature heating device in step (2) is a tube furnace, the atmosphere is oxygen, and the gas flow rate is 50 cfm to 300 cfm. Otherwise, a muffle furnace is used, and the atmosphere is air.
7. A multi-doped and coated composite layered positive electrode material as claimed in claim 1, characterized in that: The particle diameter of the multi-doped and coated composite layered positive electrode material is 1 μm to 15 μm, wherein the Al element doping amount is 0.2% to 5% of the amount of the layered positive electrode material, the Ti element doping amount is 0.2% to 5% of the amount of the layered positive electrode material, the sulfur anion doping amount is 0.2% to 5% of the amount of the layered positive electrode material, and the Li2SO4 coating amount is 0.5% to 5% of the amount of the layered positive electrode material.
8. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery adopts a multi-doped and coated composite layered positive electrode material as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Positive-electrode material for lithium-ion secondary battery, method for producing same, and lithium-ion secondary battery
CN107112531A
High-nickel ternary positive electrode material and preparation method thereof
CN111244397A
Dual-effect modified lithium ion battery high-nickel positive electrode material and preparation method thereof
CN113314700A
High-capacity single-crystal positive electrode material and preparation method thereof
CN113437289A
Li2SO4-coated and Al-doped composite layered positive electrode material and application thereof
CN115332497A
